Gibbons syn på forholdet mellem Rom og de kristne - Christiansen, Erik (Religionsvidenskabeligt Tidsskrift, 1991)
Edward Gibbon is often quoted for stating Christianity as the main cause for the fall of the Roman Empire, although a proper reading of his book proves that Christianity - or rather "the abuse of Christianity" - to him is only one of several "secondary" causes. In the main this article os a presentation of Gibbon's view on early Christianity and the persecutions of the Christians (chapters XV-XVI). I conclude by saying that Gibbon has a distance to Christianity which enabled him to see how and why the non-Christian surroundings and the Roman authorities reacted as they did, as often overlookedd but very important point of view, which actually makes Decline and Fall of the Roman Empire - in spite of its age - much more in conformance with present scholarly debate on the question that many contributions published in between.